2020
DOI: 10.3389/fped.2020.00556
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Palliative Care Birth Planning as Advance Care Planning

Abstract: Purpose of Review: A significant number of pregnancies are complicated by a fetus with a life-limiting diagnosis. As diagnoses are made earlier in the pregnancy, families experience anticipatory grief and are faced with navigating goals of care for a baby that has yet to be born. With the support of the care team, families can begin to grieve, plan, and make meaningful memories during the duration of the pregnancy, the birth of their baby, and life of the child. Creating a palliative care birth plan, which exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 80 publications
0
37
0
2
Order By: Relevance
“…While research from the United States, Australia and Europe has recommended structured perinatal palliative care programmes for families who choose to continue a pregnancy with foetal anomalies (Cortezzo et al, 2020; Flaig et al, 2019; Guimarães et al, 2019; O’Donoghue, 2019; Weeks et al, 2020), following TOPFA many parents have reported feeling inadequately supported. Specifically, concerns have included a lack of relevant information to inform decision‐making, inconsistent levels of support during the termination and in follow‐up, and perceived negative attitudes from healthcare professionals (Hodgson et al, 2016; Pitt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While research from the United States, Australia and Europe has recommended structured perinatal palliative care programmes for families who choose to continue a pregnancy with foetal anomalies (Cortezzo et al, 2020; Flaig et al, 2019; Guimarães et al, 2019; O’Donoghue, 2019; Weeks et al, 2020), following TOPFA many parents have reported feeling inadequately supported. Specifically, concerns have included a lack of relevant information to inform decision‐making, inconsistent levels of support during the termination and in follow‐up, and perceived negative attitudes from healthcare professionals (Hodgson et al, 2016; Pitt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…W planie powinny zostać uwzględnione procedury medyczne określone oraz wyjaśnione przez lekarza prowadzącego, procedury pielęgnacyjne oraz podział obowiązków między personel medyczny a rodziców ustalony i zaakceptowany przez obie strony, określenie potrzeb rodziców względem opieki nad dzieckiem, w tym potrzeb religijnych, a także ich własnych potrzeb, np. w zakresie opieki psychologicznej [13]. W najtrudniejszym momencie, jakim jest zgon noworodka, należy dać rodzicom czas na pożegnanie, a także zapewnić im odpowiednie warunki, tak by uszanować rozpoczęcie procesu ich żałoby.…”
Section: Dyskusjaunclassified
“…The increased use of prenatal diagnostics has led to a growing number of diagnoses of life-limiting fetal conditions [ 1 , 2 , 3 ]. Learning about a severe fetal condition is devastating and traumatic [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Parents react with shock, distress, and feelings of disbelief [ 11 ].…”
Section: Introductionmentioning
confidence: 99%